Quantification of Pelvic Tilt in Total Hip Arthroplasty - Zhu, Jinjun (Springer-Verlag, 2009)
In THA, anterior or posterior tilt of the pelvis changes the position of the acetabular component on the coronal plane of the body as compared with its anatomic position in the pelvic bone. To understand the occurrence and clinical importance for patients with pelvic tilt on an operating room table in the lateral decubitus position, we studied 436 patients (477 hips) undergoing primary THA using an imageless computer navigation system that measured tilt. We determined the distribution and magnitude of pelvic tilt, especially tilt of 10° or greater. The distribution of tilt had a range of 25° posterior to 20° anterior. Twenty-nine of 477 (6.1%) hips had zero tilt; 251 (52.6%) had tilt of 1° to 5°; 120 (25.2%) had tilt of 6° to 9°; and 77 (16.1%) had tilt of 10° or greater. The conversion factor for acetabular anteversion has been determined by a mathematical formula by Lembeck et al. and was confirmed by us in practice. Measurement of pelvic tilt during the performance of THA will improve the accuracy of cup position, especially allowing anteversion to be measured on the coronal plane. Level of Evidence: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.